Implementasi Prinsip Jurnalistik dan Kualitas Reportase Jurnalis Kampus Universitas Nusa Nipa: Analisis Kesenjangan Teori-Praktik - Kedoh, Lodowik Nikodemus (Peneliti.net, 2025)
The implementation of journalistic principles and the quality of reportage are essential for journalists to present accurate, credible, and relevant information, while also developing professional skills and building the campus media's reputation as a trusted news source within the university and the broader community. This study analyzes the performance of campus journalists at Nusa Nipa University, identifying three main issues: the gap between theoretical understanding and journalistic practice, limited development of essential journalistic skills, and challenges in producing high-quality reportage. Findings reveal that although journalists theoretically understand basic principles such as the 5W and 1H, their application in the field remains suboptimal, as reflected in shallow reports and inaccurate quotations. Both technical and non-technical competencies vary among journalists due to a lack of continuous training, hindering mastery of in-depth interviewing and on-camera presentation. In addition, campus journalists struggle to cope with time pressure and unexpected field conditions during coverage, resulting in reports lacking depth and context—further worsened by limited supporting equipment. Nevertheless, the positive potential demonstrated by some members indicates that, with proper guidance and support, the quality of campus journalism practice can be significantly improved, preparing more competent young journalists.